Imbalances, Inequality and Growth – Rethinking Growth Policies for Europe - László Andor (Intereconomics, 2016)
Positive GDP growth is important, but how much GDP growth we need and how the growth of income should be distributed are equally important questions. This explains why (for reasons of distribution and environmental sustainability) a movement has developed over the last ten years to go "beyond GDP". Progress has been made in measuring the social and environmental impact of growth, which has helped in the development of EU objectives like achieving smart, sustainable and inclusive growth.
Keywords: 330